Color temperature line: forward and inverse transformation - Qasim, N.H.; Pyliavskyi, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2020)
In the calculations, colorimetric calculations using different types of light sources used are the black body line and the family of isothermal lines, but the coordinates of the light source are determined by a schedule or set of color coordinates. When using modern models of color type CAM02, CAM16, it is necessary to promptly receive the light source coordinate data, knowing its color temperature. The paper proposes an analytical expression that binds the color temperature dependence and its location in the system Yxy. The presented results cover the Kelvin temperature range from 1080 to 10,000 K. The algorithm has a certain conversion error, which is shown in the figures, but when evaluating its magnitude, it was determined that these errors are beyond the threshold of human visibility. The paper presents results that can be used in the construction of modern adaptive systems for the source of illumination of photo and video transmission systems. The data describing the color body lines under different vision adaptation conditions are presented, which will allow considering these features in new systems, to make the perception of visual information maximum under different viewing conditions, from ordinary to extreme ones. The use of isothermal lines extends the functionality of the listed areas of application and simplifies working with them.